Penerapan UU No. 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak di Wilayah Kabupaten Pamekasan - Umi Supraptiningsih (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2019)
The problems of children are increasing and increasingly diverse. It causes them to be classified as Children in Conflict with Law (ABH), either as perpetrators or victims. The problems are sexsual crime, theft, scuffelling, mugging, and drug addictive cases.The existance of Law No. 11 of 2012 concerning the Act of Children Criminal Justice System (UU-SPPA) in lieu of Law No. 3 of 1997, is expected to give more rights to ABH. UU-SPPA has been implemented as it has been stated in the Act, such as the implementation of Diversification as regulated in the UU-SPPA and also Supreme Court Regulation No. 4 of 2014 concerning Guidelines for the Implementation of Diversity in the Children Criminal Justice System (UU-SPPA). The judges spesialized for Juvenil courts are already available, but the prosecutors and the police are not yet available. During the legal process, ABH is not detained except in certain cases (ultimum remidium). However, the implementation of the decision cannot be carried out perfectly due to the unavailability of facilities and infrastructure which are mandated by the SPPA, such as vocational training institutions, the Child Welfare Organization (LPKA).